Prospective Comprehensive Genomic Profiling of Advanced Gastric Carcinoma Cases Reveals Frequent Clinically Relevant Genomic Alterations and New Routes for Targeted Therapies. (16th April 2015) - Ali, Siraj M.; Sanford, Eric M.; Klempner, Samuel J.; Rubinson, Douglas A.; Wang, Kai; Palma, Norma A.; Chmielecki, Juliann; Yelensky, Roman; Palmer, Gary A.; Morosini, Deborah; Lipson, Doron; Catenacci, Daniel V.; et al.
Abstract: Background: Gastric cancer (GC) is a major global cancer burden and the second most common cause of global cancer-related deaths. The addition of anti-ERBB2 (HER2) targeted therapy to chemotherapy improves survival for ERBB2 -amplified advanced GC patients; however, the majority of GC patients do not harbor this alteration and thus cannot benefit from targeted therapy under current practice paradigms. Materials and Methods: Prospective comprehensive genomic profiling of 116 predominantly locally advanced or metastatic (90.0%) gastric cancer cases was performed to identify genomic alterations (GAs) associated with a potential response to targeted therapies approved by the U.S. Food and Drug Administration or targeted therapy-based clinical trials. Results: Overall, 78% of GC cases harbored one clinically relevant GA or more, with the most frequent alterations being found in TP53 (50%), ARID1A (24%), KRAS (16%), CDH1 (15%), CDKN2A (14%), CCND1 (9.5%), ERBB2 (8.5%), PIK3CA (8.6%), MLL2 (6.9%), FGFR2 (6.0%), and MET (6.0%). Receptor tyrosine kinase genomic alterations were detected in 20.6% of cases, primarily ERBB2, FGFR2, and MET amplification, with ERBB2 alterations evenly split between amplifications and base substitutions. Rare BRAF mutations (2.6%) were also observed. One MET -amplified GC patient responded for 5 months to crizotinib, a multitargeted ALK/ROS1/MET inhibitor. Conclusion: Comprehensive genomic profiling of GC identifies clinically relevant GAs that suggest benefit from targeted therapy including MET -amplified GC and ERBB2 base substitutions. Abstract : Prospective comprehensive genomic profiling of 116 predominantly locally advanced or metastatic gastric cancer (GC) cases was performed to identify genomic alterations (GAs) associated with a potential response to targeted therapies or targeted therapy-based clinical trials. Comprehensive genomic profiling of GC identified clinically relevant GAs that suggest benefit from targeted therapy including MET -amplified GC and ERBB2 base substitutions.